HYDROGEN DIPLOMACY AND GEOPOLITICS OF ENERGY TRANSFORMATION - Svitlana O. Fedulova; Kyrylo I. Reziapov (European Vector of Economic Development)
The research is devoted to the issues of determining the EU’s long-term strategic choice in the context of energy transformation and studying the key elements of the EU’s hydrogen diplomacy. The main idea of the paper is to assess the key elements of the EU’s hydrogen diplomacy at the moment in the context of the geopolitics of energy transformation. The potential key centres of hydrogen production in Europe has been identified in the paper. The study also highlights that the EU plans to become an importer of green hydrogen and Power-to-X products. Hydrogen is likely to have a significant impact on the geography of energy trade, further regionalising energy relations. It should also be borne in mind that pure hydrogen will not generate profits comparable to today’s oil and gas. Hydrogen is a transformation, not an extraction, and it has the potential to be produced competitively in many places. It is argued that there is an urgent need to transform the EU’s hydrogen diplomacy in the paper, aligning Europe’s interests in enhancing its competitiveness and energy security in times of crisis with global goals of decarbonisation and sustainable economic development. The implementation of effective hydrogen diplomacy and partnerships within the H2-diplo initiative will consolidate the geopolitical and security environment on the way to the EU’s strategic autonomy. At the same time, it is noted that the EU needs to think deeply about the potential contribution of the EU to territorial defence and deterrence in the paper and how its defence instruments can strengthen the Atlantic Alliance’s deterrence and territorial defence strategy. This refocusing on traditional defence will significantly increase the EU’s added value. The National Security Strategy, approved by the Biden administration on 12 October 2022, makes this clear, distinguishing between China as a ‘systemic’, ‘global’ challenge and russia as an ‘immediate’, albeit more local, threat. It has been explaind that as the United States increases its focus on China and Asia, Europe will have to assume more responsibility for the security and defence of the continent.